2022
DOI: 10.1177/17455057221116505
|View full text |Cite
|
Sign up to set email alerts
|

Respectful maternity care and associated factors among mothers who gave birth at public health institutions in South Gondar Zone, Northwest Ethiopia 2021

Abstract: Introduction: Respectful maternity care is essential for improving maternal and neonatal health. Lack of respectful maternity care during childbirth services is one of the deterrents to women seeking facility-based deliveries. It is a health system failure and a violation of women’s rights. There is limited data on respectful maternity care during childbirth and maternity care in Ethiopia, particularly at rural health facilities. But studies have shown that many women from rural areas were more likely to repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Women with unintended pregnancies had a 2.3 times higher likelihood of experiencing disrespect during labor. Consistent with the ndings of the present study, Ferede et al also reported a higher incidence of disrespect among women with unwanted pregnancies [55]. The Bante study found that planned pregnancies tripled the odds of receiving Respectful Maternity Care (RMC) [56].…”
Section: Discussionsupporting
confidence: 89%
“…Women with unintended pregnancies had a 2.3 times higher likelihood of experiencing disrespect during labor. Consistent with the ndings of the present study, Ferede et al also reported a higher incidence of disrespect among women with unwanted pregnancies [55]. The Bante study found that planned pregnancies tripled the odds of receiving Respectful Maternity Care (RMC) [56].…”
Section: Discussionsupporting
confidence: 89%
“…Care that is provided with in a kind and friendly approach to women, using polite words, calling the woman by her name, and speaking the language the mother understands, it is measured by using seven requirements. A woman who answered “Yes” to all seven questions regarding friendly care was considered to have received it during labor and delivery ( 11 , 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to the 2016 Ethiopia Demographic and Health Survey (EDHS) report, Ethiopia has one of the highest maternal mortality ratios (MMRs) globally, with 412 maternal deaths occurring per 100,000 live births ( 10 ). A negatively perceived quality of care in facility-based childbirth often prevents the use of facility-based delivery services, both in the present or in the future ( 11 ). According to a recent evaluation conducted in Ethiopia, 85% of the 103 surveyed women reported that their service experience had impacted their decision regarding their future place of delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Daytime delivery (adjusted odds ratio: 0.47, 95% confidence interval: 0.25-0.89), cesarean section (adjusted odds ratio: 0.69-6.08), and other factors. Respectful maternity care was substantially linked with (adjusted odds ratio: 1.9, 95% confidence interval: 1.33-2.72) [40]. Only 7% women had a negative birth experience.…”
Section: Study Selectionmentioning
confidence: 98%